Comcot 1.7 Modeling To Estimate The Maximum Height And Arrival Time Of The Tsunami In Tombariri Sub-District - Bakri, Abu; Angmalisang, Ping Astony; Kemer, Kurniati; Patty, Wilhelmina; Pamikiran, Revols Dolfi CH; Taher, Nurmeilita (Sam Ratulangi University, 2025)
Tombariri Sub-District is located on the North Coast of the Minahasa Peninsula, directly opposite the North Sulawesi Subduction. North Sulawesi subduction has the potential for earthquakes with a targeted magnitude of M8.5 that can generate tsunamis. In addition, Tombariri Sub-District has a fairly large population density and is located on the coast. This causes the Tombariri Sub-District to be highly vulnerable to tsunami hazards. This study aims to determine the tsunami's estimated maximum height and arrival time. The modeling method in this study is through the Comcot 1.7 application with the worst-case scenario of North Sulawesi Subduction M8.5. The results of this study showed that the maximum height of the tsunami reached 6.17 m. The estimated time of tsunami arrival in Tombariri District ranges from 5-10 minutes. The results of this study can be used as a means of mitigating tsunami disasters. Keywords: Comcot, Tsunami Modeling, Inundation, Numeric Simulation Abstrak Kecamatan Tombariri terletak di wilayah Pesisir Utara Semenanjung Minahasa yang berhadapan langsung dengan Subduksi Sulawesi Utara. Subduksi Sulawesi Utara memiliki potensi gempabumi dengan magnitudo tertarget M8.5 yang dapat membangkitkan tsunami. Selain itu, Kecamatan Tombariri memiliki kepadatan penduduk yang cukup besar dan berada di wilayah pesisir. Hal ini menyebabkan Kecamatan Tombariri memiliki tingkat kerawanan terhadap bahaya tsunami yang tinggi. Penelitian ini bertujuan untuk mengetahui estimasi ketinggian maksimum dan waktu tiba tsunami. Metode pemodelan dalam penelitian ini melalui aplikasi Comcot 1.7 dengan skenario terburuk Subduksi Sulawesi Utara M8,5. Hasil dari penelitian ini menunukkan bahwa tinggi maksimum tsunami mencapai 6,17 m. Estimasi waktu tiba tsunami di Kecamatan tombariri berkisar antara 5 - 10 menit. Hasil dari penelitian ini dapat digunakan sebagai sarana mitigasi bencana tsunami. Kata Kunci : Comcot, Pemodelan tsunami, Simulasi Numerik.